The Impact of a Plant-Based Diet on Gestational Diabetes: A Review - Antonio Schiattarella; Mauro Lombardo; Maddalena Morlando; Gianluca Rizzo (Antioxidants, 2021)
Gestational diabetes mellitus (GDM) represents a challenging pregnancy complication in which women present a state of glucose intolerance. GDM has been associated with various obstetric complications, such as polyhydramnios, preterm delivery, and increased cesarean delivery rate. Moreover, the fetus could suffer from congenital malformation, macrosomia, neonatal respiratory distress syndrome, and intrauterine death. It has been speculated that inflammatory markers such as tumor necrosis factor-alpha (TNF-α), interleukin (IL) 6, and C-reactive protein (CRP) impact on endothelium dysfunction and insulin resistance and contribute to the pathogenesis of GDM. Nutritional patterns enriched with plant-derived foods, such as a low glycemic or Mediterranean diet, might favorably impact on the incidence of GDM. A high intake of vegetables, fibers, and fruits seems to decrease inflammation by enhancing antioxidant compounds. This aspect contributes to improving insulin efficacy and metabolic control and could provide maternal and neonatal health benefits. Our review aims to deepen the understanding of the impact of a plant-based diet on oxidative stress in GDM.